PRE CONSTRUCTION AND POST FAILURE OF SLOPE DAM STABILITY ON SAFETY FACTOR ANALYSIS (A REVIEW) - Reza P. Munirwan (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Abstract: The article describes about the failure story of dam due to lack of stability. Carsington Dam in Derbyshire UK had been chosen as case study for this paper. The data obtain in the analysis was a part of postgraduate study project of the author. This dam failure is an example of an end-of-construction failure in an earth-fill slope brought from deficiency of design. In term of stability for pre-construction analysis, soil parameters of drained shear strength are used based on the original designer. In terms of porewater pressure, because there are no assumption values by the designer can be found as information in literature, range values of ru are used in the analysis. For safety factor calculation, SLOPE program version 18.2 was used follow with wedge analysis method for comparison purpose. Next, for post-failure analysis, the soil parameters combinations between peak, post-peak and residual were used to calculate the factor of safety. From the analysis of initial failure, the dam’s designer used peak strength parameters whereas for post-failure, residual strength parameters was used in boot and yellow clay, and peak strength in the boot. The safety factor at the time of failure was approximately 0.901.Keywords : earth-fill, slope, pre-construction, post-failure.Abstrak: Artikel ini menjelaskan tentang proses keruntuhan bendungan air dikarenakan oleh tingkat stabilitas lereng yang rendah. Bendungan Carsington di Derbyshire UK dipilih sebagai studi kasus untuk tulisan ini. Data yang digunakan untuk analisis adalah merupakan bagian dari studi magister dari penulis. Keruntuhan bendungan ini adalah contoh nyata dari keruntuhan pada saat akhir konstruksi dikarenakan ketidaktepatan dalam perencanaan. Berdasarkan analisis kestabilan dari tahap konstruksi, perencana menggunakan parameter kuat geser terdrainase. Parameter tekanan air pori digunakan nilai-nilai asumsi ru dikarenakan tidak diperolehnya data mengenai parameter tekanan air pori dalam literatur. Angka keamanan lereng dianalisis menggunakan program SLOPE versi 18.2 dan dibandingkan dengan cara konvensional yaitu dengan analisis bagian. Analisa pasca keruntuhan lereng menggunakan data tanah yang merupakan kombinasi dari nilai puncak, pasca-puncak dan residual untuk menghitung kestabilan lereng. Berdasarkan analisa awal, perencana bendungan menggunakan nilai maksimum dari parameter tanah, sedangkan dari hasil analisa pasca keruntuhan diperoleh parameter tanah yang dugunakan adalah nilai residual pada kaki dan material tanah lempung kuning dari lereng, dan juga parameter desain maksimum pada kaki bendungan. Angka keamanan yang diperoleh pada saat keruntuhan lereng terjadi diperoleh yaitu 0.901.Kata kunci : bendungan, lereng, sebelum konstruksi, keruntuhan pasca.